2019
DOI: 10.3846/btp.2019.05
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study on learning organization as an essential action lowering skill mismatch effects

Abstract: Skill mismatch phenomenon has been discussed in various scientific journals as it is proven to lower productivity and weaken competitiveness. Understanding the skill mismatch effect on competitiveness leads to a new way of thinking about how to manage skill mismatch for the organization sustainability. Previous researches recognize the concept of organizational management in order to be able to compete by creating a learning organization environment. Adhering to the learning organization principles, individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This study examines far transfer in the sense that in developing countries like Pakistan, management training is being imparted on the basis of western theories and practices but most of the people at workplace in Pakistan are Pakistanis and believe in Islam as source of best management theory and practice. The survey conducted at the end of the courses to assess training effectiveness revealed that most of the participants regarded their management training programs, designed by the power sector Authority of the country, as irrelevant to their organizational cultures (Dewi et al, 2019) . This is broadly consistent with already prevailing disillusionment with management education in developed countries like USA and Great Britain (Jones, 1989) and sometimes with management development programmes in developed (Shipton & Shackleton, 1998) as well as developing countries.…”
Section: Outcome Variable: Transfer Of Trainingmentioning
confidence: 99%
“…This study examines far transfer in the sense that in developing countries like Pakistan, management training is being imparted on the basis of western theories and practices but most of the people at workplace in Pakistan are Pakistanis and believe in Islam as source of best management theory and practice. The survey conducted at the end of the courses to assess training effectiveness revealed that most of the participants regarded their management training programs, designed by the power sector Authority of the country, as irrelevant to their organizational cultures (Dewi et al, 2019) . This is broadly consistent with already prevailing disillusionment with management education in developed countries like USA and Great Britain (Jones, 1989) and sometimes with management development programmes in developed (Shipton & Shackleton, 1998) as well as developing countries.…”
Section: Outcome Variable: Transfer Of Trainingmentioning
confidence: 99%
“…In this context, it is obvious that there is an objective bilateral impact of the demographic dimension of globalization and the transition to a knowledge economy on the current course of migration, the redistribution of human potential among countries of the world, becoming intellectual and innovative development is conducted in works Vovkanych, Semiv (2007), Fedulova (2008), Azhazha (2008). The human capital impact determination on economic growth and increasing the competitiveness of the state, enterprise is researched in scientific works of Radionova (2009), Proshak (2008), Dewi, Dwiatmadja, Suharti (2019). Zakharova (2010), Azhazha (2008), Podra (2019) devoted their research works to the study of peculiarities of investing in human capital.…”
Section: Introductionmentioning
confidence: 99%